Feasibility of Optical Tracking for Swept Synthetic Aperture Imaging - Perez, Anet Sanchez; Javadi Eshkalak, Nazli; Bottenus, Nick (IEEE International Ultrasonics Symposium (Online), 2023)
Ultrasound imaging is a non-invasive, low-cost option for real time screening and diagnosis across several areas of healthcare. However, the use of ultrasound is often limited by low image quality of deep targets which can necessitate more expensive and invasive imaging modalities. Resolution at depth can be improved by increasing the physical dimensions of the imaging array, but this approach is restricted by system complexity. The Swept Synthetic Aperture (SSA) technique bypasses this obstacle by using the position and orientation of the ultrasound array as it is swept over a target to generate an extended effective array. Our goal is to demonstrate the feasibility of using optical tracking to record the motion of a swept transducer with sufficient accuracy and precision to improve deep target detectability. This method eliminates the need for complex and constrictive physical fixture setups, thereby offering an improved level of practicality and adaptability to the SSA technique. Optically tracked SSA images showed a significant improvement in resolution and target detectability compared to a reference image from a stationary aperture. We expect that this method will improve resolution and penetration for deep targets, especially when using smaller ultrasonic systems with limited aperture size.